Peranan Mahasiswa Dalam Bersinergi Dengan Masyarakat Pada Kegiatan KKN Padukuhan Jomblangan - Fitriyana, Mifta (Gemi: Jurnal Penelitian dan Pengabdian, 2025)
The KKN activities of Universitas Cokroaminoto Yogyakarta are routine activities held every period. In the KKN period XLIV themed "Academic and Community Synergy in Building Villages" group 8 located in Jomblangan Hamlet worked together with local residents to build the village. There are several work programs prepared by KKN students who also consulted with the hamlet and RT in Jomblangan Hamlet. The KKN activities of UCY students in Jomblangan Hamlet use a participatory approach, providing education and socialization, infrastructure development, training and empowerment. With this KKN, it is hoped that students will be able to live in society, and be able to develop skills, work together across disciplines, and apply knowledge according to their respective fields of study.